High School Mathematics Teacher’s Ability in Developing Mathematical Literacy Instrument: A Study in East Lampung Regency - Triana, Mella; Siregar, Erimson (FKIP Universitas Lampung, 2020)
High School Mathematics Teacher’s Ability in in Developing Instruments of Mathematical Literacy Test: Study in Lampung Timur Regency. This study aims to describe the ability of high school mathematics teachers in East Lampung Regency in developing instruments of mathematical literacy test. This research is a descriptive study with 19 respondents of high school mathematics teachers. The research data were obtained through test, performance test and questionnaires. Data analyzed using data reduction, data presentation and conclusion. The results showed that: a) 63.16% teachers only able to create routine problem which measure employing stage in mathematical process; b) male teachers with more than 25 years teaching experience are only able to develop 5.26% mathematical problems which measure formulating stage; c) Reasoning and argument is the fundamental mathematics skills that was rarely measured in the developed instrument; d) using symbolic, formal and technical language and operations is the most frequently skills that is measured in the developed instrument. Keywords: mathematical literacy instrument, high school teacher, descriptive research. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp35-48